2020
DOI: 10.1108/ijpdlm-06-2019-0201
|View full text |Cite
|
Sign up to set email alerts
|

Management strategies for supply risk dependencies: empirical evidence from the gulf region

Abstract: PurposeThe purpose of this study is to propose a conceptual model for managing supply risk (SR) dependencies in regional supply networks (SNs). Grounded on resource dependency theory (RDT), the research conceptualises the management of SR as buffering and bridging strategies that enable organisations to redefine their SN to cope with SR and as a three-stage transformation mechanism. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 71 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…Moreover, we applied the RDT towards studying SCRES in a pandemic setting and empirically confirmed the theories' suitability for research in unpredicted supply environments ( Al-Balushi and Durugbo, 2020 ). Based on our findings, we can acknowledge that different governance mechanisms can help companies to cope with such a challenging situation ( Pfeffer and Salancik, 1978 ).…”
Section: Conclusion Implications and Future Researchmentioning
confidence: 68%
See 1 more Smart Citation
“…Moreover, we applied the RDT towards studying SCRES in a pandemic setting and empirically confirmed the theories' suitability for research in unpredicted supply environments ( Al-Balushi and Durugbo, 2020 ). Based on our findings, we can acknowledge that different governance mechanisms can help companies to cope with such a challenging situation ( Pfeffer and Salancik, 1978 ).…”
Section: Conclusion Implications and Future Researchmentioning
confidence: 68%
“…Both approaches can be simultaneously applied to manage dependencies in an individual relationship ( Al-Balushi and Durugbo, 2020 ). Moreover, Manhart et al (2020) showed that firms leveraging both buffering and bridging strategies to manage their resource dependencies achieve higher firm performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies of RLM in times of normality suggest the adoption of intra-and inter-regional strategies for economic development and environmental sustainability with goals of boosting operational resilience (Durugbo et al, 2020b). The RLM focus on crisis in this study is unique and reflects recent crisis-driven challenges within studies of cross-functional integration (Poberschnigg et al, 2020), high reliability organisations (Sawyerr and Harrison, 2019), logistics service network design (Dufour et al, 2018), and supply risk dependencies in supply networks (Al-Balushi and Durugbo, 2020).…”
Section: Managing Regional Logisticsmentioning
confidence: 99%
“…RLM offers an on-going and contemporary focus for management scholarship, yet there are limited studies exploring conventional RLM strategy (e.g. Al-Balushi and Durugbo, 2020;Demirbag et al, 2020) and far fewer studies concentrating on RLM strategy in times of crisis. Additionally, a scrutiny of the HLSC literature suggests a gap in knowledge on RLM and potential priorities that underpin crisis-driven RLM strategies for HLSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, bridging—as opposed to buffering, which occurs outside of a supplier relationship—aims to mitigate uncertainty through cross-border measures such as sharing of information, joining an alliance, or further strategies that enhance the power of a buyer in a relationship ( Bode et al, 2011 ). Both strategies can be used in parallel to manage dependencies in one relationship ( Al-Balushi and Durugbo, 2020 ).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%